SPARC- experimental fusion device - Kelhar, Tim (Matrika, 2021)
SPARC is a new fusion energy experiment, for which expectations are set pretty high in the science community. It will be using the most modern technology, from high temperature superconductors to ion cyclotron heating. It will be operating using the most promising fusion fuel, deuterium-tritium. SPARC will have 10 times smaller volume than ITER, and still manage to have a gain factor higher than 2, thanks to its strong magnetic field, high plasma currents and the sole option for heating - ion cyclotron heating. Its construction is projected to start this year, 2021.
Keywords: eksperimentalni reaktorji; experimental reactors; fusion reactors; fuzijski reaktorji; jedrska fizika; nuclear physics; SPARC; SPARC experiment